2017
DOI: 10.1016/j.jmb.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding Function of PI3Kgamma Emerges from Enzyme's Shadow

Abstract: Traditionally an enzyme is a protein that mediates biochemical action by binding to the substrate and catalyzing the reaction that translates external cues into biological responses. Sequential dissemination of information from one enzyme to another facilitates signal transduction in biological systems providing for feed-forward and feedback mechanisms. Given this view-point, an enzyme without its catalytic activity is generally considered to be an inert organizational protein without catalytic function and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 73 publications
(100 reference statements)
0
7
1
Order By: Relevance
“…We provide strong data for a critical scaffolding role for the noncatalytic, N-terminal domain of PI3K and its interaction with TRPV4 in mediating myofibroblast transdifferentiation. The N terminus of PI3K contains an amino acid sequence that is not homologous to that of the other class I PI3Ks (19). Although we found that the noncatalytic, N-terminal PI3K domain was required for the formation and translocation of TRPV4-PI3K complexes and for myofibroblast transdifferentiation, our data do not exclude the possibility that PI3K and PI3K also play additional, potentially redundant, roles that require their enzymatic activities in fibroblast activation (54,55).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…We provide strong data for a critical scaffolding role for the noncatalytic, N-terminal domain of PI3K and its interaction with TRPV4 in mediating myofibroblast transdifferentiation. The N terminus of PI3K contains an amino acid sequence that is not homologous to that of the other class I PI3Ks (19). Although we found that the noncatalytic, N-terminal PI3K domain was required for the formation and translocation of TRPV4-PI3K complexes and for myofibroblast transdifferentiation, our data do not exclude the possibility that PI3K and PI3K also play additional, potentially redundant, roles that require their enzymatic activities in fibroblast activation (54,55).…”
Section: Discussioncontrasting
confidence: 73%
“…Class I PI3Ks are composed of a regulatory subunit (p85) and a catalytic subunit (p110). The catalytic activity of p110 resides in the C-terminal portion of the protein; the N-terminal domain has no catalytic activity and has a unique sequence and tertiary structure compared to the corresponding regions of the other class I PI3K catalytic subunits (19). To more clearly define the functional domain of PI3K that was involved in its interaction with TRPV4, we tested full-length, wild-type PI3K (p110), a PI3K (p110) mutant including only the noncatalytic N-terminal domain (AA 1-142), or a PI3K (p110) mutant with deletions of the N-terminal domain and the adenosine triphosphate (ATP) binding site (N-del, AA 1-142, AA 948-981) for binding to and activation of TRPV4 (Fig.…”
Section: The Noncatalyic N-terminal Domain Of Pi3k Is Necessary and ...mentioning
confidence: 99%
“…These kinase-independent adapter or scaffolding functions appear highly selective since the absence of a particular PI3K isoform is unlikely to be restored by remaining ones, and for unknown reasons was clearly documented only for the GPCR-dependent PI3-kinases. Kinase-independent functions may act in concert or may be interconnected with the kinase activity, like PI3Kγ in diet-induced obesity and PI3Kβ in insulin signaling or they may act independently from each other, as shown by PI3Kγ in cardiac contractility [99,100,101,102,103].…”
Section: Non-catalytic Functions Of Pi3kγmentioning
confidence: 99%
“…Kinase-independent functions for PI3Kγ were described in other physiological contexts [102]. The kinase-independent link between PI3Kγ and the PDE/PKA axis was proposed to play a role in microglial responses after focal brain ischemia [109,110], and in the regulation of cAMP response element-binding protein (CREB)-mediated transcriptional responses in noradrenergic neurons of the locus coeruleus [47].…”
Section: Non-catalytic Functions Of Pi3kγmentioning
confidence: 99%
“…The involvement of PI3Kγ and GRK2 rather suggests specific compartmentalized signalling pathways downstream of G i PCR. Indications for tight compartmentation of signalling responses mediated by PI3Kγ and GRK2 have been gathered in diverse cellular systems (Mohan & Naga Prasad, 2017; Watson et al, 2016). Both PI3Kγ and GRK2 are activated by direct interaction with the βγ‐subunits of G i PCR (Eichmann et al, 2003; Hawkins & Stephens, 2015; Ribas et al, 2007).…”
Section: Discussionmentioning
confidence: 99%